URBAN SUFISM Kajian Fenomenologis terhadap Kecenderungan Bertasawuf Masyarakat Kota Palangka Raya - Rahman, Fadli (LP2M IAIN Palangka Raya, 2009)
The design of the study is early started from the observation on spiritualism movement â especially on the urban sufism â which becomes a phenomenon at the 21st century. In the metropolitan area, includingPalangkaRayaCity, the urban sufism trend phenomena dynamically occurs slowly. The trend can be seen from the emerging of the Islamic study groups, Islamic discussion groups, dzikir groups and so forth which are flooded by urban society.The aim of this phenomenological study is to explore the real occurrence behind the urban sufism phenomena inPalangkaRayaCity. Methodologically, the study makes the followers of Islamic sufism groups as the informant. Besides, the study places the sufism teachers as the key informant. In terms of data collection, the techniques used in the study were participatory observation, in depth interview, and library research. The study applied domain and taxonomy analyses to analyze the data.The result of the study showed that there was an increasing number of sufism religious life in Palangka Raya society. This trend could be seen from the increasing number of the Islamic study groups, Islamic discussion groups, dzikir groups and so forth characterized by the while shirts dominantly for both rural society and educated people. The sufism trend was affected by three integrated domain factors: religious practices, psychological, and social factors. Second, specifically, each of the three factors was divided into: 1) Religious domain, including the wish to study religious values, and spiritual hunger, looking for or try to get meaningful life, through religious line, understanding the Islamic law, and balancing world and hereafter factors. 2) Psychological domain was consisted of stress and depression in life, and looking for or try to get the spiritual peace. 3) Social domain was consisted of prestige and spiritual trend globally spread out, which was considered as a merely factor. Third, the trend of urban Sufism life inPalangkaRayaCitywas mostly affected by nuance factors or on religious domain.Â